Role of Cell Surface Hydrophobicity in the Pathogenesis of Medically-Significant Fungi - Danchik, Carina; Casadevall, Arturo (Frontiers in Cellular and Infection Microbiology, 2021)
Cell surface hydrophobicity (CSH) is an important cellular biophysical parameter which affects both cell-cell and cell-surface interactions. In dimorphic fungi, multiple factors including the temperature-induced shift between mold and yeast forms have strong effects on CSH with higher hydrophobicity more common at the lower temperatures conducive to filamentous cell growth. Some strains of Cryptococcus neoformans exhibit high CSH despite the presence of the hydrophilic capsule. Among individual yeast colonies from the same isolate, distinct morphologies can correspond to differences in CSH. These differences in CSH are frequently associated with altered virulence in medically-significant fungi and can impact the efficacy of antifungal therapies. The mechanisms for the maintenance of CSH in pathogenic fungi remain poorly understood, but an appreciation of this fundamental cellular parameter is important for understanding its contributions to such phenomena as biofilm formation and virulence.